1995
DOI: 10.1111/j.1545-5300.1995.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducational Multiple Family Groups: Four‐Year Relapse Outcome in Schizophrenia

Abstract: Earlier studies of family psychoeducation and clinical reports on multiple family groups (MFGs) have reported substantial reductions in relapse rates for patients with schizophrenia. These groups offer an expanded social network and thereby may confer a margin of protection against relapse. However, to date, there has not been an empirical trial of this modality. The advent of family psychoeducational and behavioral management strategies provided the basis for an experimental, three-way comparison of psychoedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
1
5

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(124 citation statements)
references
References 34 publications
1
117
1
5
Order By: Relevance
“…The two studies that compared family treatment and routine care both found significantly lower relapse or rehospitalization rates associated with family treatment Zhang, Wang, Li, & Phillips, 1994). Three studies compared multiple-family groups and single-family interventions (Leff, Kuipers, Berkowitz, & Sturgeon, 1985;McFarlane, Link, Dushay, Marchal, & Crilly, 1995;McFarlane, Lukens, et al, 1995). The two studies by McFarlane et al reported lower relapse rates for the multiple-family group format than for single-family therapy (based on Anderson, Reiss, & Hogarty's, 1986, model), whereas Leff et al (1990) reported no differences between the two formats.…”
Section: Efficacy Statusmentioning
confidence: 99%
“…The two studies that compared family treatment and routine care both found significantly lower relapse or rehospitalization rates associated with family treatment Zhang, Wang, Li, & Phillips, 1994). Three studies compared multiple-family groups and single-family interventions (Leff, Kuipers, Berkowitz, & Sturgeon, 1985;McFarlane, Link, Dushay, Marchal, & Crilly, 1995;McFarlane, Lukens, et al, 1995). The two studies by McFarlane et al reported lower relapse rates for the multiple-family group format than for single-family therapy (based on Anderson, Reiss, & Hogarty's, 1986, model), whereas Leff et al (1990) reported no differences between the two formats.…”
Section: Efficacy Statusmentioning
confidence: 99%
“…Programs differ in organization and content (individual family psychoeducation, individual family psychoeducation with group psychoeducation for relatives, family psychoeducation groups 44,45 .…”
Section: Types Of Psychoeducation Programsmentioning
confidence: 99%
“…MFG has been found to improve the management of other psychiatric and neurological conditions (e.g., schizophrenia, traumatic brain injury) and decrease health care usage (Dyck et al, 2002;McFarlane, 2002;McFarlane, Link, Dushay, Marchal, & Crilly, 1995;Rodgers et al, 2007). In this intervention, we modified the standard MFG format of McFarlane (2002) to include formalized training in cognitive rehabilitation strategies.…”
Section: Introductionmentioning
confidence: 99%